An offer that you can't refuse? Agrimafias and migrant labor on vineyards in Southern Italy - Stefan Seifert; Marica Valente (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
In the 2011 post-Arab Spring migration wave, over 64,000 migrants landed on the southern Italian coast, with many of them potentially working illegally on farms through caporalato, a widespread system of illegal recruitment of underpaid farm labor run by Italian agrimafias. To test this hypothesis, this paper evaluates the causal effects of the 2011 migration wave on reported labor productivity focusing on vineyards in southern Italy. Based on a dynamic panel data model, labor productivity is estimated to increase by about 11% on average for 2011 and 2012. We show that this corresponds to a total of around 10 million unreported work hours, or 21,000 full-time employees, in each year. We interpret this as an increase in employment of illegal workforce due to the migration wave. Magnitude, direction, and statistical significance of the effect are confirmed under various model specifications and using synthetic control and post-lasso approaches.
Keywords: F22; J61; J43; 330; Migration wave; Agrimafias; Illegal Employment; Vineyard productivity